Promising Materials for Renewable Energy Production and Sustainable Energy Generation - Poulomi Mukherjee; Pallabi Roy; Sumana Ghosh (Research Developments in Science and Technology Vol. 1, 2022)
Materials provide encouraging ways to obtain renewable and sustainable energy for the future generation. Thermal resistant materials can increase energy productivity. In this regard, nanocoatings are being explored for improved energy efficiency in gas turbine engines. Advanced materials such as composites, engineered polymers, hybrid materials and low-density high-strength metals or alloys can improve the performance of energy production and energy transfer equipment. There is a great demand for lower cost functional materials for energy systems. Tremendous research interest has been grown on the development of new innovative materials for renewable and sustainable energy technologies. This book chapter covers various materials suitable for sustainable energy conversion, storage, and saving as well as materials required for renewable energy production. The present challenges and future scope of the existing materials have been also described. The objective of the present study is to focus various promising materials for sustainable energy generation and renewable energy production, the opportunity and benefit towards utilizing those materials.